New species of Leptohalysis (Rhizaria, Foraminifera) from an extreme hadal site in the western Pacific Ocean - Kitazato, Hiroshi; Uematsui, Katsuyuki; Todo, Yuko; Gooday, Andrew J. (Zootaxa, 2009)
Leptohalysis kaikoi sp. nov., a new hormosinacean foraminiferan, is described from a core sample collected using the Japan Agency for Marine-Earth Science and Technology’s Remote Operated Vehicle, KAIKO, in the Challenger Deep (10,896 m water depth, Izu-Bonin-Mariana-Arc-trench system). The agglutinated test is Leptohalysis in the following features: 1) the chambers are rounded and abut closely with a distinct suture between them, rather than being flask-shaped with more or less flat, truncated bases; 2) the wall structure is less regular and consists mainly of grains with flat exposed faces that abut to create an outer surface resembling an uneven pavement, the edges of the grains being obscured by copious amounts of organic cement; 3) the proloculus is sometimes followed by a single “adventitious”chamber, located to one side of the axis of growth. A second species with similar characteristics is represented by a single individual in our material. These two species may represent a new genus. However, we prefer to retain them within Leptohalysis pending a detailed comparison of their wall structure with that of typical members of this genus. We also briefly describe a single specimen of a typical Leptohalysis morphotype. Leptohalysis kaikoi sp. nov. was the most common multilocular agglutinated foraminiferan in the 32-63 µm sieve fraction of the Challenger Deep sample. It has not been found in the same size fraction of samples from abyssal depths in the North and eastern equatorial Pacific Ocean.